Avaliação dos efeitos da desinfecção química e com radiação ultravioleta na estabilidade dimensional de diferentes materiais de moldagem odontológicos - (:unkn) unknown (Universidade Brasil, 2021)
The disinfection of molds obtained with dental impression materials is within the biosafety protocols, in the control of cross-infection of microorganisms in dental offices, prosthesis laboratories, professionals and patients, being currently the target of greater attention due to the pandemic of COVID-19, with the implementation of alternative disinfection protocols and methods. The purpose of this study was to compare the effects of disinfection by ultraviolet radiation and chemical disinfection on dimensional stability of different dental molding materials. Acrylic resin mannequin molds with irreversible hydrocolloidal materials (alginate) (n = 25) and elastomer (condensation silicone) (n = 25) were used with different disinfection methods (n = 5): G1- negative control: no treatment, G2- Glutaraldehyde 2% (10 min), G3- Sodium hypochlorite 1% (10 min), G4- UV-C radiation (λ = 254 nm) (30 s), G5- Autoclave (positive control) (15 min). The molds after the treatments were cast with special plaster. After 24 h, the plaster models were measured by a calibrated, blinded researcher, with a caliper in determined places on the upper first molar: mesio-distal (MD-O) and vestibulo-lingual (VL-O) and buccal cervical-occlusal face (CV-B) and mesio-distal (MD-V). The data were tabulated and analyzed using the statistical tests of Kolmogorov-Smirnov, ANOVA one-way and Tukey tests (p <0.05). There were no statistically significant differences in the linear values of plaster models between chemical (Glutaraldehyde 2%, sodium hypochlorite 1%) and physical (UV-C radiation) disinfection methods with the control (p> 0.05), the autoclave showed a significant difference in relation to the control and the different methods of disinfection (p <0.05) with greater dimensional change for both impression materials. It can be concluded that the methods of chemical disinfection (Glutaraldehyde 2%, Sodium hypochlorite 1%) and physical (UV-C radiation) maintained the dimensional stability of the dental impression materials alginate and elastomer (condensation silicone).
Keywords: Alginato; Bioengenharia; Desinfecção; Elastômeros; Radiação ultravioleta; CS